Improving Adherence to ARV Therapy in person Living with HIV/AIDS (PLWHA) by The Community-Based Interactive Approach (CBIA) in Temanggung District, Indonesia - Sisilia Esti Purwaningsih; Titien Siwi Hartayu (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2026)
Adherence to antiretroviral (ARV) therapy is critical for people living with HIV/AIDS (PLWHA) since it extends life expectancy despite not curing the infection. A study in Temanggung District aimed to enhance knowledge, attitudes, and practices of PLWHA using the Community-Based Interactive Approach (CBIA-ARV). This quasi-experimental study employed a time-series pretest-posttest design with control and intervention groups, selecting participants through purposive sampling based on specific inclusion and exclusion criteria. The inclusion criteria used were Smile Plus members (≥ 18 years), PLWHA ≥1 year, receiving ARV drug therapy, not pregnant, and not experiencing communication barriers. Exclusion criteria were participants who could not be present during CBIA-ARV activities and participants who were not present during posttest 2 and or posttest 3. Interventions were provided using the CBIA-ARV method. The intervention significantly improved knowledge, attitudes, and practices in the intervention group across all time points: pre-post 1, 2, and 3 (knowledge: p=0.001, attitudes: p=0.001, practices: p=0.001). In contrast, the control group showed minimal changes in knowledge and attitudes initially, with significant improvements appearing only in attitudes and practices later (p=0.001). Comparing both groups, significant differences emerged post-intervention in knowledge, attitudes, and practices at various stages (p<0.05). The study concluded that the CBIA-ARV approach effectively enhances PLWHA’s knowledge and attitudes, proving to be a valuable method for improving treatment adherence in this population.